Understanding transport-related social exclusion: a multidimensional approach - Yigitcanlar, Tan; Afzan, Mohamed; Md., Kamruzzaman; Piracha, Awais (2019)
Transport-related social exclusion (TRSE) is a common problem across the globe. Despite TRSE has been identified to be a multifaceted concept, researchers often focus on a single dimension to identify individuals/groups facing exclusion, which leaves most of the at-risk groups unidentified— due to a lack of comprehensive empirical framework. This paper reports the development of a multidimensional framework through a review of the literature and based on a Delphi survey. A range of dimensions and indicators of TRSE were identified through the review. Their suitability was assessed by the experts through a two-round Delphi survey—involving 33 international experts. These experts reached a consensus that individuals are likely to face TRSE in physical, economic, temporal, spatial, psychological, and information dimensions, which can be measured by 15 key indicators consisting of 47 sub-indicators. The findings of this research serve as a guide for scholars and policymakers to understand what constitutes TRSE and act accordingly